2014
DOI: 10.21767/amj.2014.2070
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral variations of brachial plexus involving the median nerve and lateral cord: An anatomical case study with clinical implications

Abstract: In the course of routine dissection of the upper limbs of a Caucasian male cadaver, bilateral variations were observed in the brachial plexus. In the right extremity, the lateral cord was found to be piercing the coracobrachialis muscle. The musculocutaneous nerve and lateral root of the median nerve were observed to be branching inferior to the lower attachment of coracobrachialis muscle. The left extremity exhibited passage of the median nerve through the flat tendon of the coracobrachialis muscle near its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The brachial plexus has been known to exhibit variation from the typical pattern, with many anomalies that have been previously described [1][2][3][4]. The prosected anatomical donor discussed here was found to have an atypical branching pattern not noted in the literature.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The brachial plexus has been known to exhibit variation from the typical pattern, with many anomalies that have been previously described [1][2][3][4]. The prosected anatomical donor discussed here was found to have an atypical branching pattern not noted in the literature.…”
Section: Introductionmentioning
confidence: 62%
“…This seems to be a fairly typical anomaly [1]. In another instance, the lateral cord pierced the coracobrachialis muscle, and the lateral root of the median nerve branched below the attachment of the coracobrachialis on the scapula [2]. There are also cases in which the median nerve is only derived from the medial cord rather than from the medial and lateral cords [2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Henceforth awareness regarding the brachial nerves piercing the coracobrachialis is essential, to avoid inadvertent damage. 16 Restoration of elbow flexion is of surgical importance in patients with traumatic brachial plexus injuries. Therapeutic nerve grafting procedures results in successful outcomes, for restoring plexus injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Median nerve is most frequently formed by two roots: Single lateral root from the lateral cord and single medial root from the medial cord, which unite anterior or lateral to the axillary artery. 1 Abhaya et al 5 and Butz et al 6 reported cases of lateral cord of median nerve piercing the coracobrachialis muscle before its bifurcation into musculocutaneous and LRMN. However, they did not describe the course of two terminal branches of lateral cord within the muscle.…”
Section: Discussionmentioning
confidence: 99%